A case of a severe factor XI deficiency in a Chinese woman with heavy menorrhagia. Issue 2 (March 2019) - Wang, Yingyu; Wang, Qingyu; Zhang, Yonggen; Ma, Ping; Ding, Hongxiang
Abstract : N/A: The current study was to elucidate the molecular defect in a 32-year-old Chinese woman with heavy menorrhagia and delayed wound healing. The F11 gene was amplified by PCR and screened for mutations. Then identified mutations were analyzed by in-silico programs and molecular modeling analysis. This woman was found to have severely low levels of factor XI (FXI) (FXI:C: 2.0%; FXI:Ag: 5.4%) by surgical screening. Further DNA sequencing of F11 reveled a novel mutation (p.Ser295Ile) in the Ap4 domain and an already known mutation (p.Trp228stop) in the Ap3 domain. Pedigree analysis showed that the new mutation was inherited from her father (FXI:C: 41%), whereas the other was inherited from her mother (FXI:C: 62%). Modeling analysis indicated Ser295Ile mutation probably determining important structural changes in the protein folding. Both of the heterozygous mutation contribute to the severe FXI deficiency by interfering with correct assembly of the region.